Scientific and construction toys in education and industry: values and interactions in Spain (1920-1936) - Guijarro, Victor (Historia y Memoria de la Educación, 2021)
This study contemplates the extension and mutual influences of certain kinds of renovating practices promoted in two realms of education, formal and non-formal, in the second and third decades of the 20th century in Spain. As part of a broader critique of the traditional school, these new perspectives coincided in their rethinking of the students’ and amateurs’) relationship with the materials used in learning process. For them, the object, rather than constituting a distant, symbolic and untouchable reality –subject to a memory-based, verbalist conception of education–, should be a close, touchable tool whose handling contributes to awakening the inventive abilities of students, especially in scientific disciplines. We will analyze the connections and differences between the principles of movements included in active teaching and the strategies of companies dedicated to the manufacture of construction toys, particularly those carried out by a preeminent brand working in this sector at the time, Meccano.